STUDIED ON ICED STORAGE OF CULTURED ROHU (LABEO ROHITA) - JOSEPH, JOSE; SURENDRAN, P K; PERIGREEN, P A (Fishery Technology, 2017)
The biochemical, bacteriological and organoleptic changes in cultured rohu (Labeo rohtta) during iced storage have been studied. Non-protein nitrogen decreased and water soluble nitrogen remained almost same during storage in ice. Initially, when the fish was in pre-rigor and rigor conditions, the extractibility of protein was low (45 to 50 %) which increased after the resolution of the rigor and the decrease in extractability towards the end of storage was insignificant. The total volatile base nitrogen remained steady upto 7 days in ice and showed slight decrease on further storage. During iced storage the bacterial count increased from 10 3 /g to 10 5 /g by the 11th day of storage. Nearly 80-90 % of the total bacterial population in fresh fish was constituted by mesophiles which decreased gradually (decreased to 1 % by 13th day of iced storage). Organoleptically the fish was acceptable upto 15 days in ice.